Limits of monetary policy autonomy by East Asian debtor central banks - Axel Löffler; Gunther Schnabl; Franziska Schobert (Center for Economic Studies and ifo Institute (CESifo), 2012)
Due to buoyant capital inflows East Asian central banks with exchange rate targets accumulate foreign reserves and thereby increase surplus liquidity. East Asian central banks with more flexible exchange rate regimes also face surplus liquidity that mainly emanates from past accumulation of foreign reserves. We show based on an augmented Barro-Gordon-type central bank loss function that in both cases surplus liquidity limits monetary policy autonomy. In case of fixed exchange rates East Asian central banks can escape from the impossible trinity and gain monetary policy autonomy by using non-market-based sterilization which leads to financial sector distortions. In a flexible exchange rate regime monetary policy autonomy can be gained without financial sector distortions by using market-based sterilization. As central banks face substantial sterilization costs as well as revaluation losses on foreign reserves, however, monetary policy autonomy is eroded.
Keywords: E52; E58; F31; 330; debtor central banks; monetary policy autonomy; sterilization; exchange rate regime; East Asia; Geldpolitik; Autonomie; Zentralbank; Währungsreserven; Gesamtwirtschaftliche Liquidität; Wechselkurssystem; Ostasien